Rumble fish - Hinton, S. E. (New York : Bantam Doubleday Dell Books for Young Readers, 1989)
A junior high school boy idolizes his older brother, the coolest, toughest guy in the neighborhood, and wants to be just like him.
Notable/Best Books (A.L.A.).
School Library Journal.
Wilson's Junior High School.
4.7
Young Adult
Keywords: Brothers -- Fiction; City and town life -- Fiction; Social problems -- Fiction; Brothers -- Fiction; City and town life -- Fiction; Social problems -- Fiction